Development screening bags onenoday implemented by parents who have toddlers - Hapsari, Wanodya; Yuliani, Diki Retno (Innovation in Health for Society, 2022)
This research was carried out by implementing onenoday development screening bags by parents with toddlers. Implementation of the media is needed to assess the product used. Developmental delays can be caused by a lack of concern for parents in carrying out stimulation, early detection, and intervention. So far, mothers under five have used the Mother and Child Health book as a medium for inspiration and early detection of child development. Unfortunately, the use of MCH book media by mothers under five is in the less category, and parents do not read MCH books for various reasons. Providing stimulation by providing traditional counselling before makes the material unacceptable. Therefore, this study proposes the implementation of a no-day development screening bag to assess parents' response to the product. This research design is descriptive and quantitative. The research sample was 30 parents with children under five in the working area of the Kalimanah Health Center. Incidental sampling technique. The instrument is in the form of a questionnaire, a Likert scale measurement scale. The data obtained is analyzed by calculating the percentage of answers to the questionnaire for each item. The results showed that it was easy to use 86.7%, instructions for use were clear 84.2%, users felt interested 87.5%, felt enthusiastic and motivated 85.8%, easy to understand material 83.8%, gained knowledge about early detection of toddler development 85.8%, could use 89.2%. We concluded that onenoday, parents with toddlers can implement development screening bags. Keywords: Child care; innovation in pediatrics; child development; health education; healthcare system